Pengaruh Fly Ash Tempurung Kelapa Sebagai Bahan Tambah Terhadap Kuat Tekan Dan Kuat Lentur Beton - Gunawan, Andi Candra; Setiawan, Arman; Yuniarto, Eka (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
The world of construction is currently experiencing very rapid development. This can be seen from various countries that are competing to improve the quality and quantity of their buildings. The purpose of this study was to determine the effect of adding coconut shell fly ash to the concrete mix with variations of 5%, 10%, and 15% by weight of cement on the compressive strength and flexural strength of concrete. There were 38 samples made, including 20 samples of normal concrete and 18 samples of variation concrete. Concrete samples were soaked for 28 days prior to testing the compressive strength and flexural strength of the concrete. The results of the compressive strength test with the addition of 5% fly ash were (26.11 Mpa), 10% (27.34 Mpa), and 15% (29.23 Mpa) while for flexural strength with the addition of 5% fly ash (3.73 Mpa), 10% (3.78 Mpa), and 15% (3.91 Mpa). The results of this test indicate that the variable concrete has a higher compressive strength and flexural strength than normal concrete. the use of coconut shell fly ash in the concrete mixture, greatly affects the compressive strength and flexural strength of concrete compared to normal concrete.